Antileishmanial in vitro activity of essential oil from Myrciaria plinioides, a native species from Southern Brazil - Kauffman, Carla (2019)
Universidade do Vale do Taquari. Centro de Ciências Biológicas e da Saúde. Lajeado, RS, Brasil.